The Level of Thinking Skills in the Reading Section of EFL Textbook in Indonesia - Soni Ariawan; Muh Azhar Kholidi; Mulyono Putra (VELES Voices of English Language Education Society, 2023)
The curricular implementations are represented in the textbook. The textbook is used by all students, who may have varying levels of thinking skill; however, it is a good opportunity to encourage students, regardless of their critical thinking skill level, to not only learn to know and understand, but also to apply, evaluate, and create such a product from their learning. The present study aims to investigates the level of thinking skills employed in the reading parts of EFL textbooks in Indonesia. The Ministry of Education and Culture officially printed the textbook for senior high school students in grade X. Content analysis was used to explore the level and frequency of thinking skills, focusing on the task and reading questions in the textbook. The data were quantitatively displayed in the form of a table. It was gained through the coding process based on the theoretical framework of Low Order Thinking Skills (LOTS) and High Order Thinking Skills (HOTS) introduced by Bloom. It was found that the textbook mostly included knowledge and comprehension levels of thinking in the reading tasks and questions. It means that LOTS-based tasks and questions are more dominant than HOTS.